Neutralizing Activity of Anti-interferon-γ Autoantibodies in Adult-Onset Immunodeficiency Is Associated With Their Binding Domains - Yasamut, Umpa; Thongkum, Weeraya; Moonmuang, Sutpirat; Sakkhachornphop, Supachai; Chaiwarith, Romanee; Praparattanapan, Jutarat; Wipasa, Jiraprapa; Chawansuntati, Kriangkrai; Supparatpinyo, Khuanchai; Lai, Ethan; Tayapiwatana, Chatchai (Frontiers in Immunology, 2019)
Autoantibodies to interferon-γ (IFN-γ) are associated with severe disseminated opportunistic infections that are presumably a result of their neutralizing activity. However, the characteristics of the neutralizing antibodies in patients are poorly defined. To better understand the properties of the anti-IFN-γ autoantibodies (anti-IFN-γ autoAbs) in patients with opportunistic infections, a simplified competitive-binding ELISA was developed. The “actual” neutralizing anti-IFN-γ autoAbs were assessed based on their competition with commercial neutralizing mouse anti-IFN-γ monoclonal antibodies (mAbs). First, the binding affinity and neutralizing capacity of these mAbs (clones B27, B133.5 and MD-1) were characterized. Kinetic analysis and epitope binning using bio-layer interferometry showed the comparable binding affinity of these mAbs to full-length IFN-γ and to the adjacent binding region. These mAbs did not recognize the synthetic 20-mer peptides and inhibited IFN-γ-mediated functions differently. In a competitive-binding ELISA, the anti-IFN-γ autoAbs in AOID serum blocked B27, B133.5 and MD-1 mAb binding. This evidence suggested that the autoAbs that competed with these mAbs were neutralizing antibodies and that they recognized a discontinuous epitope of homodimeric IFN-γ. The patient autoAbs that recognized the B27 epitope exhibited strong neutralizing activity. Our results demonstrated the heterogeneity of the autoAbs against IFN-γ in AOID patients and the different patterns among individuals. These data expand upon the fundamental knowledge of neutralizing anti-IFN-γ autoAbs in AOID patients.